LIMITASI WAKTU PENEGAKAN HUKUM DALAM PROSES PELANGGARAN PEMILIHAN KEPALA DAERAH DI INDONESIA - Munte, Herdi; Tommi, Missiniaki (Ensiklopedia of Journal, 2023)
Abstract: Regional Head Elections (Pilkada) represent the embodiment of people’s sovereignty at the regional level. However, their implementation is often marked by various violations and criminal acts, such as money politics, voter data manipulation, and abuse of power by public officials. This study employs a normative legal research method using the statute and conceptual approaches to analyze the effectiveness of law enforcement against Pilkada-related crimes under Law Number 10 of 2016. The main focus is the time limitation in criminal investigations, which affects legal certainty and substantive justice. The findings reveal that the 14-day investigation limit aims to promote efficiency and legal certainty in the criminal justice system. Nevertheless, practical challenges remain, including limited resources and weak inter-agency coordination, which may undermine substantive justice. Therefore, reformulating the criminal law policy in Pilkada is essential to ensure that efficiency does not compromise justice and human rights.Keywords: Regional Election, Law Enforcement, Time Limitation.